2001
DOI: 10.1115/1.1413466
|View full text |Cite
|
Sign up to set email alerts
|

Transient Pig Motion Through Gas and Liquid Pipelines

Abstract: Simulation of the transient motion of pigs through liquid and gas pipelines is presented. The differential form of the mass and linear momentum equations for compressible liquid and gas flows were solved by a finite difference numerical technique. The fluid flow equations were combined with a linear momentum equation for the pig and a model for bypass flow through the pig. The pig/wall contact forces were simulated by a stick/slip model. The contact forces developed by disk pigs and the pipe wall were predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 2 publications
1
22
0
3
Order By: Relevance
“…donde a=∂P/∂ρ| T es la velocidad del sonido isotérmica, β =(-1/ ρ ) ∂ρ/∂T| P es el coeficiente de expansión térmica y el parámetro ξ es ξ =1+ρ a Nieckele et al (2001). El principio de conservación de cantidad de movimiento lineal es expresado como:…”
Section: Modelado Matemáticounclassified
See 1 more Smart Citation
“…donde a=∂P/∂ρ| T es la velocidad del sonido isotérmica, β =(-1/ ρ ) ∂ρ/∂T| P es el coeficiente de expansión térmica y el parámetro ξ es ξ =1+ρ a Nieckele et al (2001). El principio de conservación de cantidad de movimiento lineal es expresado como:…”
Section: Modelado Matemáticounclassified
“…Nieckele et al (2001), presentaron un modelo para la simulación del movimiento de pigs. Las ecuaciones de conservación fueron combinadas con la ecuación del pig y estas, a su vez, resueltas utilizando el método de diferencias finitas.…”
Section: Introductionunclassified
“…Some other researchers also reported their results of pigging simulation in twophase flow straight pipelines (Minami and Shoham, 1991;Taitel et al, 1989;Scoggins and M. W. 1977;Xiao-Xuan and Gong, 1999). Nieckele et al (2001) presented isothermal transient pigging operation through gas and liquid pipelines. Nguyen et al (2001b) proposed a computational scheme using method of characteristics (MOC) and a regular rectangular grid for estimating the pig dynamics when it flows in natural gas pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Some other complementary research was also reported for pigging simulation in two-phase flow straight pipelines [5][6][7][8]. Transient pig motion through gas and liquid pipelines was presented by [9]. Modeling and simulation for pig flow control in a natural gas pipeline was studied by [10].…”
Section: Introductionmentioning
confidence: 99%